160 Anticipatory prescribing in community end of life care: systematic review and narrative synthesis of the evidence since 2017. (14th March 2023) - Bowers, Ben; Antunes, Bárbara; Etkind, Simon; Hopkins, Sarah; Winterburn, Isaac; Kuhn, Isla; Pollock, Kristian; Barclay, Stephen
Abstract : Background: The anticipatory prescribing of injectable medications is recommended practice in controlling distressing symptoms in the last days of life. A 2017 systematic review found practice and guidance was based on inadequate evidence. Since then, the evidence base has changed significantly, warranting a new review. Aim: To review the evidence published since 2017 concerning anticipatory prescribing of injectable medications for adults at the end of life in the community. Methods: Systematic review and narrative synthesis: Nine literature databases were searched from May 2017 to March 2022, alongside reference, citation and two journal hand searches. Gough's Weight of Evidence framework was used to appraise the robustness and relevance of studies. PROSPERO registration 42016052108. Results: Twenty-eight papers were included in the synthesis. Evidence published in the last five years shows that the standardised prescribing of four medications for anticipated symptoms is commonplace in the UK; evidence of practices in other countries is limited. There is inadequate data on how often medications are administered in the community. The prescribing of anticipatory medications appears to be a significant event for patients and signifies the imminence of death. Prescriptions are accepted by family caregivers despite inadequate explanations, and they generally appreciate having access to medications. Robust evidence of the clinical and cost-effectiveness of anticipatory prescribing remains absent. Conclusion: The evidence underpinning anticipatory prescribing practice and policy remains based primarily on healthcare professionals' perceptions that the intervention offers reassure and provides effective, timely symptom relief in the community. There is still inadequate evidence about likely symptom profiles and which anticipatory medications and dose ranges are needed. The views and experiences of patients and their family caregivers towards anticipatory prescribing need further investigation. Urgent research is necessary to investigate the clinical effectiveness, cost-effectiveness, safety and acceptability of different anticipatory prescribing practices.